Hepatitis B and measles seroprevalence among Turkish children - Kanra, Güler; Tezcan, Sabahat; Badur, Selim; Study Team, Turkish National (The Turkish Journal of Pediatrics, 2005)
This study was performed to determine hepatitis B and measles seroprevalence among the population under 30 years of age in Turkey. Blood samples of 2,683 subjects from eight provinces of Turkey were studied. Measles IgG was determined by hemagglutinin inhibition method, and hepatitits B surface antigen (HBsAg), anti-hepatitis B surface antibody (anti-HBs) and anti-hepatitis B core antibodies (anti-HBc) were determined by ELISA method. Overall seropositivity for measles was found to be 59.6%. There was a significant difference in seropositivity among provinces. The seropositivity was found to increase with age. The overall seropositivities for HBsAg, anti-HBs and anti-HBc were found to be 5.4%, 17% and 15.1%, respectively. The seroprevalences differed significantly among provinces. Although seroprevalence for anti-HBs and anti-HBc increased with age, HBsAg seropositivity did not change significantly after one year of age. Seroprevalence was not affected by sex. It was concluded that every effort should be given to vaccinate infants as early as possible for hepatitis B and that the coverage of infancy measles vaccination should be increased with a second dose.